(untitled) (World Bulletin of Public Health, 2022)
Inflammatory disease of the small pelvic organs is the study of the immune system of women, the analysis of its results. It was found that the decrease in T-lymphocytes showed the development of T-immunodeficiency in the immune system of sick women; A significant decrease in CD4 + cells relative to the control group and a reliable increase in CD8 + cells showed a significant increase in immune system activity. The relative and absolute amounts of CD25 + - and CD95 + - cells varied in different directions. A significant increase in the mean number of CD16 +-cells by 1.93-2.02 showed a significant increase in the role of these cells in the immune response. In women diagnosed with pelvic inflammatory disease, the relative and absolute amounts of CD38 + and CD23 + cells were significantly higher than in the control group, with 1.27 and 1.86 times the relative values and 1.21 and 1.78 times the absolute values, respectively